Exogenous Angiotensin I Metabolism in Aorta Isolated from Streptozotocin Treated Diabetic Rats - P. P. Wołkow; B. Bujak-Giżycka; J. Jawień; R. Olszanecki; J. Madej; J. Rutowski; R. Korbut (Journal of Diabetes Research)
Purpose. Products of angiotensin (ANG) I metabolism may predispose to vascular complications of diabetes mellitus. Methods. Diabetes was induced with streptozotocin (75 mg/kg i.p.). Rat aorta fragments, isolated 4 weeks later, were pretreated with perindoprilat (3 μM), thiorphan (3 μM), or vehicle and incubated for 15 minutes with ANG I (1 μM). Products of ANG I metabolism through classical (ANG II, ANG III, and ANG IV) and alternative (ANG (1–9), ANG (1–7), and ANG (1–5)) pathways were measured in the buffer, using liquid chromatography-mass spectrometry. Results. Incubation with ANG I resulted in higher concentration of ANG II (P = 0.02, vehicle pretreatment) and lower of ANG (1–9) (P=0.048, perindoprilat pretreatment) in diabetes. Preference for the classical pathway is suggested by higher ANG III/ANG (1–7) ratios in vehicle (P=0.03), perindoprilat (P=0.02), and thiorphan pretreated (P=0.02) diabetic rat. Within the classical pathway, ratios of ANG IV/ANG II (P=0.01) and of ANG IV/ANG III (P=0.049), but not of ANG III/ANG II are lower in diabetes. Conclusions. Diabetes in rats led to preference toward deleterious (ANG II, ANG III) over protective (ANG IV, ANG (1–9), and ANG (1–7)) ANG I metabolites.